Pengembangan Sistem Pengukur Curah Hujan di Sungai Jakarta Berbasis IoT - Hendra Rahmawan; Dary Muzhar Muhammad; Farianto (Jurnal Ilmu Komputer dan Agri-Informatika, 2022)
DKI Jakarta is a lowland with high rainfall intensity in certain periods. Currently rainfall is measured manually by officers by visiting directly the Ombrometer rainfall gauge which is placed at a number of points close to several rivers in Jakarta. With such a procedure, the measurement of rainfall becomes inefficient in terms of time and cost because it requires officers who have to visit the measurement location directly and require several additional processes to get the measurement value. This will be difficult if rainfall data is needed in real time, such as for flood early warning purposes. To overcome this problem, a rainfall measuring system is needed that can measure rainfall automatically and send the measurement results in real time via the internet. In this research, an IoT-based rainfall measuring system has been developed using the waterfall method which consists of the stages of defining requirements, designing system, implementing system, and testing system. The system is based on a tipping bucket rainfall sensor whose value can be read and processed directly by the IoT NodeMCU ESP8266 device. The test results have shown that all the functional requirements of the system that have been defined can function properly.